TEACHING LEARNING PROCESS OF ENGLISH AT THE SIXTH YEAR OF SD N GUMPANG 1 KARTASURA: AN EDUCATIONAL ETHNOGRAPHY - Rokhmawati, Haniefah Nur (2004)
This research paper is proposed at knowing the teaching learning process of English at the sixth year of SD Negeri Gumpang 1 Kartasura in 2003/2004 academic year. The problem of the study is how is the teaching learning of English at the sixth year of SD N Gumpang 1 Kartasura in 2003/2004 academic year. To describe the teaching learning process of English in the classroom, the writer uses an educational ethnography as the type of research. The data used in this research are divided from event, informant, and document. The data are quoted from the interview and observation. From the research finding, the objective of teaching in SD covers 2 goals; the general instructional objective is based on the decree of regional office at DEPDIKBUD Number 308/103.a/1995 and the specific instructional objective is to introduce English as the first foreign language and to prepare the student to have English skill to continue to the higher level. The Curriculum is 1994 English local content curriculum and they use topic-based syllabus. The teacher uses textbook and pictures as the material to support the activity in the classroom. The classroom activities have almost focused to the four language skills. The teacher has roles as a manager, facilitator, consultant or a counselor, instructor and evaluator, while, the student's role as the object of the study. The classroom procedure consist of three parts namely Engage, Study and Activate. The Evaluation in SD Negeri Gumpang 1 Kartasura are: periodic test, middle semester test and final semester test. The writer also found the strengths of the teaching learning process of English at the sixth year of SD Negeri Gumpang 1 Kartasura are in the students, the teacher, the material and the facilitation. And for the weaknesses are in the students, the teacher and the material. Finally, the outcome of this research is the most of the components in teachig learning process of English at the sixth year of SD N Gumpang are suitable to the theories of the experts.